Portraying the Spirit’s Personality to Minahasan Christian with its Ancestral Spirits Tradition Hues - Christar Arstilo Rumbay (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This essay attempts to portray the Spirit's personality to Minahasan Christian with its ancestral spirits tradition. Minahasan culture contains rich beliefs and rituals relate to ancestral spirits activities. This work prepares Minahasan Christian's practice such as kampetan, foso, mu'kur, and mumper together with the Spirit's personality throughout the Scripture. In the next stage, the Spirit's personality seeks an opportunity to engage with Minahasan Christian. However, intelligence, wisdom, and skill of the Spirit share possibility and constructive contribution toward ancestral spirit beliefs of Minahasan Christian. On the flip side, Minahasan culture openly receives works, characters, features, and impacts rather than a real figure and appearance of the Spirit. In conclusion, the Spirit's personality is not in conflict with the indigenous tradition. In contrast, it offers a new perspective and acts as a companion or partner of ancestral spirits tradition.